The Relationship between Vocabulary Mastery and Reading Performance - Yani Adyawardhani (Jurnal Bahasa Inggris Terapan, 2017)
This study investigates the relationship between students’ vocabulary knowledge and their reading performance. It aims at finding out whether vocabulary knowledge correlates with reading performance. The data was taken from final semester examination marks of Vocabulary 2 and Reading 2 subjects of 30 second semester students studying English, which was analyzed using Pearson correlation formula. The result shows that there is a slight correlation between the two subjects. Some possible causes of this result and some other educational implications are also discussed. Keywords: reading and vocabulary; the relationship between vocabulary and reading; vocabulary; reading